Behavior of the IPSA and fundamental value: an analysis of cointegration 2004-2011 - Gregoire C, Jorge; Ríos C, Jorge (Estudios de Administración, 2011)
This research is focused on the market value of IPSA´s stocks and whether those values are aligned with their fundamentals or not, along the period 2004-2011. For that purpose the article is supported by the models of Blanchard and Watson (1982), Diba and Grossman (1988); the econometrical part of the paper makes use of the vector cointegration method of Johansen (1988). The results show that market values of IPSA´s stocks cointegrates with earnings per share, IMACEC and S&P500, that is there exists a long run equilibrium relation between IPSA and its fundamentals, and the error correction model also shows that these fundamentals permit the adjustments to the short run deviations from long run equilibrium.